Solution for Roots of x^3-7x+7=0: Week #340 Nov 13th, 2018 POTW

  • MHB
  • Thread starter anemone
  • Start date
In summary, the equation x^3-7x+7=0 has a solution of x=1. To solve this equation, one can use the Rational Root Theorem and synthetic division to find the rational roots, and then use polynomial long division or the Factor Theorem to factor the equation and find the remaining roots. Other methods such as the cubic formula or graphing can also be used, but may be more complex and time-consuming. In real life, this equation can be applied in fields such as engineering and physics to determine the trajectory of a projectile under the effects of gravity.
  • #1
anemone
Gold Member
MHB
POTW Director
3,883
115
Here is this week's POTW:

-----

Given that $a,\,b$ and $c$ are roots for the equation $x^3-7x+7=0$.

Evaluate $\dfrac{1}{a^4}+\dfrac{1}{b^4}+\dfrac{1}{c^4}$.

-----

Remember to read the https://mathhelpboards.com/showthread.php?772-Problem-of-the-Week-%28POTW%29-Procedure-and-Guidelines to find out how to https://mathhelpboards.com/forms.php?do=form&fid=2!
 
Physics news on Phys.org
  • #2
Congratulations to the following members for their correct solution:

1. castor28
2. Olinguito
3. lfdahl
4. kaliprasad

Solution from castor28:
Let us write $u=\dfrac1a$, $v = \dfrac1b$, $w = \dfrac1c$, $t(n) = u^n + v^n + w^n$. We want to find $t(4)$.

$u$, $v$, and $w$ are roots of the reciprocal equation $7x^3 - 7x^2 + 1 = 0$. $u^n$, $v^n$, $w^n$ and therefore $t(n)$ satisfy the corresponding linear recurrence relation $7x_n= 7x_{n-1} - x_{n-3}$.

We have $t(0) = 3$ (obvious), $t(1) = 1$ (by Viete's relations). We compute:
\begin{align*}
t(2) &= u^2 + v^2 + w^2\\
&= (u+v+w)^2 - 2(uv+uw+vw)\\
&= 1^2 - 2\cdot0\\
&= 1
\end{align*}

We can now use the recurrence to compute:
\begin{align*}
t(3) &= t(2) - \frac{t(0)}{7} = 1 - \frac37 = \frac47\\
t(4) &= t(3) - \frac{t(1)}{7} = \frac47 - \frac17 = {\bf \frac37}
\end{align*}

Alternative solution from Olinguito:
$a,b,c$ are roots of $x^3-7x+7=x(x^2-7)+7=0$

$\implies\ a^2,b^2,c^2$ are roots of $\sqrt x(x-7)+7=0$

$\implies$ they are roots of $x(x-7)^2=49$

$\implies$ they are roots of $x^3-14x^2+49x-49=0$

$\implies$ they are roots of $x(x^2+49)=14x^2+49$

$\implies\ a^4,b^4,c^4$ are roots of $\sqrt x(x+49)=14x+49$

$\implies$ they are roots of $x(x+49)^2=(14x+49)^2$

$\implies$ they are roots of $x^3-98x^2+1029x-2401=0$

$\implies\ \dfrac1{a^4},\dfrac1{b^4},\dfrac1{c^4}$ are roots of $\dfrac1{x^3}-\dfrac{98}{x^2}+\dfrac{1029}x-2401=0$

$\implies$ they are roots of $2401x^3-1029x^2+98x-1=0$

$\implies \dfrac1{a^4}+\dfrac1{b^4}+\dfrac1{c^4}=\dfrac{1029}{2401}=\boxed{\dfrac37}$.
 
Back
Top